PENGARUH STORE ATMOSPHERE DAN PRICE FAIRNESS TERHADAP KEPUASAN PELANGGAN DI TOKO NYONYA FASHION KOTA MANNA KABUPATEN BENGKULU SELATAN - Intansari, Hutila; Bustami, Taufik (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
This research aims to determine "The influence of store atmosphere and price fairness on customer satisfaction at the Nyonya Fashion store, Manna City, South Bengkulu Regency". Both partially and simultaneously. The type of research used is quantitative research. The population of this study was 130 people who had shopped at least twice at the Nyonya Fashion store, Manna City, South Bengkulu Regency, using the Incidental Sampling technique.       The collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique used to answer the hypothesis is multiple regression. The results of this research show that: (1) the research results show a positive influence of the Store Atmosphere variable on Customer Satisfaction. Based on the results of the partial test, the t count was 2.454 and the regression coefficient was 0.307 with a significance of 0.015. (2) research results: There is a positive influence of the Price Fairness variable on Customer Satisfaction. Based on the results of the partial test, the t count was 8.479 and the regression coefficient was 1.357 with a significance of 0.000. (3) Simultaneous or joint test results obtained by Store Atmosphere and Price Fairness have a positive effect on Customer Satisfaction. This is proven by the test results obtained by the calculated f value of 140.309, with significance (0.000<0.050). Keywords : Store Atmosphere, Price Fairness, Customer Satisfaction.